The Thermodynamics of Quantum Yang-mills Theory : Theory and Applications. - Hofmann, Ralf (World Scientific, 2011)
This book aims to provide advanced students and researchers with the text on a nonperturbative, thermodynamically grounded, and largely analytical approach to four-dimensional Quantum Gauge Theory. The terrestrial, astrophysical, and cosmological applications, mostly within the realm of low-temperature photon physics, are treated.